BTP‐Rh@g‐C3N4 as an efficient recyclable catalyst for dehydrogenation and borrowing hydrogen reactions. (10th November 2021) - Luo, Lan; Liu, Hongqiang; Zeng, Wei; Hu, Wenkang; Wang, Dawei
Abstract: Highly active catalysts play an important role in modern catalysis. A novel and efficient ligand benzotriazole‐pyrimidine (BTP) and the corresponding rhodium composite on C3 N4 were successfully synthesized. The resulting rhodium composite was fully characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), x‐ray diffraction (XRD), thermogravimetric analysis (TGA), and x‐ray photoelectron spectroscopy (XPS). The obtained composite exhibited good catalytic activity and good recovery performance in the synthesis of quinoxaline from 2‐aminobenzyl alcohol and benzonitrile, and more than 20 quinoxalines were obtained in good yields. Additionally, it also showed that rhodium composite could achieved good catalytic performance in the synthesis of functionalized ketone through borrowing hydrogen strategy. Abstract : Benzotriazole‐pyrimidine and corresponding rhodium composite supported on g‐C3 N4 were synthesized and characterized by SEM, TEM, XRD, and XPS. The resulting composite showed good catalytic activity for the synthesis of arylquinazoline and functionalized ketones in high yields with good recovery performance through dehydrogenation and borrowing hydrogen strategies.